Penerapan Keselamatan Kerja Dengan Metode Fault Tree Analysis (FTA) Untuk Meningkatkan Produktivitas Kerja Di Pd. Sinar Mekar - Mohammad Fadli Perdana2; Boy Man; Asep Hermawan; Haris Sandi Yudha; roban, roban (Jurnal Teknologika, 2023)
Sinar Mekar is a business engaged in the production of sills. Like other companies, UD Sinar Mekar faces problems such as residual production waste that is around the work floor which is very disturbing in the production process which can cause work accidents which can have a negative impact on employee productivity and safety. Then the amount of ventilation is lacking, so that employees feel uncomfortable at work, and are not enthusiastic about carrying out their activities. Insufficient lighting results in the worker's eyes not being able to see clearly during the cutting process and results in the worker's finger being hit by the cutting knife. This research is to find out the factors that cause work accidents at UD. Sinar Mekar using Fault Tree Analysis (FTA) and safe T score calculation. Based on the results of calculations in 2018, there were 3 accident victims at work, namely, 1 person in January did not put the item properly so that when working, the foot fell over the item, 1 person in March Worked jokingly which resulted in a pallet being squeezed, 1 person in December Not using a mask. In 2019, there were 4 accident victims at work, namely 1 person in January. Affected by a doctor blade, 1 person in March. Working while joking which resulted in a pallet being squeezed, 1 person in August Not wearing PPE, finger exposed to caterpillars, 1 person in October, eyes often get stuck dust. In 2020 there were 2 accident victims at work, namely, 2 people in April with 2 incidents where the material was installed incorrectly, they did not use PPE.